Hybridization of Cuckoo Search and Firefly Algorithms to Calculate the Interaction Parameters in Phase Equilibrium Modeling Problems - Abdelkarim Merzougui; A. Hasseine; S. Regab; D. Laiadi (Iranian journal of chemistry & chemical engineering, 2020)
Liquid-liquid equilibrium (LLE) problems such as phase stability analysis, phase equilibrium calculations, chemical equilibrium calculations, binary interaction parameter identification of thermodynamic models and other problems of fluid characterization have been the core subject of many recent studies. This study introduces Cuckoo Search (CS), Firefly Algorithms (FA) and its variants as parameter identification methods for modeling the activity coefficients of 30 ternary systems using the NRTL and UNIQUAC models. In addition, we analyze and compare the performance of these algorithms to that of the other algorithms. The results show that the hybridization of CS and FA performs better in both speed and accuracy than similar problems based on the other met-heurists methods.